(untitled) (Revista de Ciências Agroveterinárias, 2006)
What is observed in several biomes is a search, sometimes incompatible, of finding a model that seeks to explore the biodiversity in a larges cale and in maintainable ways of the biome itself. I say incompatible because one thing is to explore it for the local population; for the communities that live there and explore their resources for years and that don’t represent threats to its conservation; different, however, is the exploration to attend demands in National or even International scales. In this last case, exploring the biodiversity in their ambient is almost always not sustainable and the cultivation and the handling plans are therein recommended. The use of the biodiversity has therefore a fundamental component in what refers to the size of the activity. At the measure that the Ministry of Health impla nts the National Politics of Medicinal and Aromatic Plants seeking medicines in the Unique System of Health-SUS, the scenery changes completely. The bio diversity starts to have an address! The scale is potentially big and needs productive systems which, besides supplying quality and homogeneous materials, they should contribute to the preservati on of the involved species, by avoiding the extractivism. That theme has interesting unfoldings and it involves in full the more studied species giving them great pulse for their use. After all, n ow more than ever, the population hopes to have such products available at SUS. In this context we will enhance the quality procedures that permeate the whole agricultural productive chain of that basic material destined to the fitomedicaments.